Management Of Penetrating Incision Wounds In The Larynx - Fiandani, Gilang Hadi; Yusuf, Muhtarum (Journal of Neonatal Surgery, 2025)
Background: Laryngeal trauma is rare. This case report discusses rare cases of penetrating incision wounds to the larynx with a psychiatric history that have successfully undergone 3.0 mm reconstruction and reconstructive surgical management. Case: A male patient, 34 years old, with a history of controlled mental disorders, came in with a cut wound to the neck through the larynx. From local state, open incision wounds with flat edges 18 cm long, wound width 3 cm, depth 8 cm, and active bleeding. The patient is planning tracheotomy and laryngeal reconstruction. Tracheotomy is performed by intubation through an open incision wound. Reconstruction is performed by splicing the inferior epiglottis tissue using absorbable thread size 3.0, followed by the closure of cartilage tissue and the posterior cricoarytenoid muscle. Furthermore, the splicing of m. platysma, m. sternohyoid, m. omohyoid, and m. The thyrohyoid was cut with an absorbable suture of 3.0 mm. Skin closure is done with simple suture stitches with non-absorbable thread size 3.0. Postoperative evaluation on day 8 showed that the results of the slippery epiglottis FOL examination did not reveal crusty suture areas, an airy airway, symmetrical vocal cord movements, edema in the posterior commissure, arytenoids, and left ventricular plica. Evaluation two weeks after reconstruction revealed that the neck surgery wound was dry and closed, the stoma from the tracheotomy had closed, and there were no complaints of difficulty swallowing. Consequently, the Naso Gastric Tube was released. Conclusion: Laryngeal reconstruction surgery on penetrating incision wounds on the larynx has been successfully performed with good results without any side effects.